2022
DOI: 10.1111/1541-4337.12928
|View full text |Cite
|
Sign up to set email alerts
|

Edible oleogels as solid fat alternatives: Composition and oleogelation mechanism implications

Abstract: The growing awareness of the adverse health effects of trans‐fats and saturated fats are driving researchers to seek healthy alternatives. A promising strategy to structure liquid oil, called oleogelation, has been a subject of great interest. In the development of oleogels, highly unsaturated oils can be structured through different gelation mechanisms by varying structuring agents (e.g., polymeric or low molecular weight oleogelators). Due to their potential to reduce saturated fat in food products while als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(21 citation statements)
references
References 195 publications
(229 reference statements)
0
21
0
Order By: Relevance
“…Meanwhile, 720 cm À1 revealed the association with (CH 2 ) n alkyl chain band in fish oil. Li et al (2022) reported the presence of van der Waals forces that were also involved in the stabilisation of oleogel structure. The structure of oleogel, which was partially crystalline and generated from the formation of hydrogen bonds with wax was emphasised (G ómez-Estaca et al, 2019).…”
Section: Ft-ir Spectrometrymentioning
confidence: 99%
“…Meanwhile, 720 cm À1 revealed the association with (CH 2 ) n alkyl chain band in fish oil. Li et al (2022) reported the presence of van der Waals forces that were also involved in the stabilisation of oleogel structure. The structure of oleogel, which was partially crystalline and generated from the formation of hydrogen bonds with wax was emphasised (G ómez-Estaca et al, 2019).…”
Section: Ft-ir Spectrometrymentioning
confidence: 99%
“…The main structures are formed by the hydrogen bonding, covalent, ionic, and Van der Waals interactions (Pehlivanoğlu et al., 2018). The type and concentration of gelator used, along with the cooling and shear rate, significantly impact the physical characteristics of oleogels (Li et al., 2022). Oleogels have been successfully employed to encapsulate retinyl palmitate and fish oil (Rehman et al., 2014; Tian & Acevedo, 2018).…”
Section: Encapsulation Of Omega‐3 Fatty Acid‐rich Oilsmentioning
confidence: 99%
“…7−9 For cosmetic goods, oleogels can improve product storage stability. 6 The advantage of bioactive substance encapsulation in oleogels is leveraged in pharmaceutical development and medical efficacy-controlled release. 10 Moreover, the oleogel emulsion is one of the most widely used systems.…”
Section: Introductionmentioning
confidence: 99%